Enteral nutrition management: Key factors and application gaps in the best clinical practice guidelines (2016)
Introduction: Adequate nutrition-support clinical practice requires recommendations based on the best available evidence, in order to help health professionals making decisions concerning the management of enteral nutritional support in pathologies of interest. Objective: To identify the key factors in the management of enteral nutrition, in order to prevent and treat malnutrition based upon the recommendations made in the best Practice Guidelines (CPG). Methods: A structured search of nutritional support in CPG was performed. Five referees independently selected the CPG among those published between 2005 and 2015. They used AGREE II in order assess quality and selected those CPG with a score no lower than 60% in the domains of methodological rigor and editorial independence. The findings were compared to the Colombian clinical practice. Results: 24 GPC were evaluated, of which 79.1% (n = 19) were developed by scientific societies, 12.6% (n = 3) by government agencies and 8.3% (n = 2) by CPG developing bodies. Selected CPG were those produced by NICE (global score 92%), and those developed by CENETEC, which scored 70.89% and 87.2%.8. Discussion: In order to decrease clinical-practice heterogeneity, take into account new therapeutic options and provide quality care, it is suggested to adopt the best CPG, such as those developed by governmental institutions and CPG developing agencies like CENETEC and NICE. Attention and implementation of their recommendations in Colombia has been poor, as the most consulted CPG are the ASPEN and ESPEN ones. Conclusion: Key elements recommended in the best nutrition CPG, are: income nutritional screening, nutritional risk monitoring, nutritional support for malnourished patients, nutritional support for patients with limiting food intake, specialized nutritional support, nutrition education, and creation of institutional nutrition committees. These elements would be useful to build societal trust in clinical practice. Encouraging consultation of high quality nutrition CPG would help to optimize capacities in the face of technical limitations in the health sector.